Economic foundations of law - Spurr, Stephen J. (Thomson/South-Western, 2006)
Easily apply economic analysis to the law with ECONOMIC FOUNDATIONS OF LAW! With numerous examples, this economics text incorporates interesting applications that bring economics to life. Applications include the market for lawyers, the proposed market for transplantable human organs, the market for adoptions, the market for bail bonds, the effects of MeganÂ's law, issues of racial profiling, the decline of the Shakers, rules used in the whaling industry